Inflammatory Bowel Disease: A Nationwide Study of Hip Fracture and Mortality Risk After Hip Fracture. (14th March 2020) - Bartko, Johann; Reichardt, Berthold; Kocijan, Roland; Klaushofer, Klaus; Zwerina, Jochen; Behanova, Martina
Abstract: Background and Aims: With rising rates of inflammatory bowel diseases [IBD] in older adults, management of comorbidities such as osteoporosis is becoming increasingly important. Hip fracture [HF] is the most serious consequence of low bone mineral quality and is associated with excess risk of mortality. For older IBD patients, there are only limited data available. Therefore, we aimed to assess the association of IBD with HF, and all-cause mortality risk after HF, among IBD patients older than 50 years. Methods: In a national database-registered case-control study, 56 821 HF cases aged ≥50 years, and 113 718 age-, sex- and region-matched non-hip-fracture controls, were analysed between 2012 and 2016. A history of IBD was assessed from data from Austrian social health insurance funds. Logistic regression and Cox proportional multivariate models were used to test the association of IBD with HF and post-hip fracture mortality risk. Results: A total of 531 patients were identified with IBD (25.0% men, mean age 81.2 years, standard deviation [SD] 9.7). Analysis, adjusted for anti-osteoporotic treatment, use of glucocorticoids, and selected medications, showed that IBD patients had an increased odds of HF (odds ratio [[OR] 2.22, 95% confidence interval [CI] 1.86–2.64). Patients with Crohn's disease [CD] revealed a higher HF odds in contrast to patients with ulcerative colitis [OR 2.91, 95% CI 2.17–3.89 and OR 1.89, 95% CI 1.52–2.35, respectively]. Overall mortality risk after HF was higher among female CD patients [HR 1.75, 95% CI 1.28–2.41] than in the general population. Conclusions: IBD was strongly associated with HF in older patients. Post-hip fracture mortality risk was elevated particularly in women with CD.